2017
DOI: 10.1093/humrep/dex023
|View full text |Cite|
|
Sign up to set email alerts
|

A Phase III randomized controlled trial comparing the efficacy, safety and tolerability of oral dydrogesterone versus micronized vaginal progesterone for luteal support in in vitro fertilization

Abstract: STUDY QUESTIONIs oral dydrogesterone 30 mg daily (10 mg three times daily [TID]) non-inferior to micronized vaginal progesterone (MVP) 600 mg daily (200 mg TID) for luteal support in in vitro fertilization (IVF), assessed by the presence of fetal heartbeats determined by transvaginal ultrasound at 12 weeks of gestation?SUMMARY ANSWERNon-inferiority of oral dydrogesterone versus MVP was demonstrated at 12 weeks of gestation, with a difference in pregnancy rate and an associated confidence interval (CI) that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
107
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 27 publications
4
107
0
5
Order By: Relevance
“…In a recent systematic review and meta‐analysis involving eight randomized clinical trials, dydrogesterone was found to be as effective as vaginal progesterone for luteal‐phase support in stimulated IVF cycles. This was also corroborated by a more recent, large, multicentric phase III trial involving 1301 randomized subjects confirming the noninferiority of dydrogesterone (30 mg/d) to micronized vaginal progesterone (600 mg/d) in the setting of conventional IVF treatment cycles . However, up to day, there are no similar studies involving dydrogesterone in the setting of FER cycles.…”
Section: Discussionmentioning
confidence: 64%
“…In a recent systematic review and meta‐analysis involving eight randomized clinical trials, dydrogesterone was found to be as effective as vaginal progesterone for luteal‐phase support in stimulated IVF cycles. This was also corroborated by a more recent, large, multicentric phase III trial involving 1301 randomized subjects confirming the noninferiority of dydrogesterone (30 mg/d) to micronized vaginal progesterone (600 mg/d) in the setting of conventional IVF treatment cycles . However, up to day, there are no similar studies involving dydrogesterone in the setting of FER cycles.…”
Section: Discussionmentioning
confidence: 64%
“…In terms of route of administration, progesterone used as LPS in our study was oral Dydrogesterone (10 mg twice daily). This route of use in the study was supported by systematic review and meta-analysis of RCT done by Barbosa et al who ended up in a conclusion that the use of oral dydrogesterone seems to be as effective as vaginal progesterone for LPS in ART cycles and appears to be better tolerated [21]; furthermore, oral route efficacy confirmed in IVF by Phase III-RCT that compares the efficacy, safety, and tolerability of oral dydrogesterone versus micronized vaginal progesterone for LPS [22]. Similar reports on equivalent efficacy were documented from RCTs in Iran and India [23,24].…”
Section: Discussionmentioning
confidence: 83%
“…One of the apparent limitations in the current trial is absence of blinding of both interventions to the patient and the investigator. In the LOTUS I trial [19] oral placebo was added to the vaginal group and a vaginal placebo was added to the oral group. Such blinding was not adopted in the current trial, as the principal secondary outcome was women's satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we intentionally restricted the routes of admin- Another limitation of the current trial was lack of data regarding the potential risk of congenital malformations. Results from the LOTUS I study found comparable rates of congenital malformations in both interventions [19]. In addition, both dydrogesterone and micronized progesterone are long-studied and well-known medications with a high safety profile [15] [16] [17] [23].…”
Section: Discussionmentioning
confidence: 99%